Seasonal dynamics of oxygen consumption and of heterotrophic bacterioplankton number in the region of the Ukrainian antarctic station Academician Vernadskiy - Chekalov, V. P. (Ukrainian Antarctic Journal, 2012)
Seasonal fluctuations of heterotrophic bacteria abundance as well as of oxygen consumption in coastal waters near island Galindez varied by levels of anthropogenic influence were investigated during wintering 2009-2010 at the Ukrainian Antarctic station Academician Vernadsky. The percentage of psychrophilic forms to mesophilic due to casual ingress of allochthonic microflora, mainly from warmblooded animals and human, was changing in a wide range. Its annual average in a relatively pure zone reached 32%, whereas it has reached 5,9 and 19,7% in two points near the station. Daily consumption of oxygen fluctuated within limits of 0,21–0,97 mg/l and it correlated more vastly with of psychrophilic microflora number (+0,835). It is shown experimentally, that the temperature factor influences rates of using oxygen more, than additional enrichment of the water environment by organic matter in areas of increased antropogenic pressure. Nevertheless, seasonal fluctuations of the number of heterotrophic bacteria and of biochemical oxygen consumption are connected to flashes of phytoplankton activity, producing considerable quantity of organic matter.